(untitled) (Heritage, 2023)
Creating and adopting local, and global strategy of socially responsible behaviour, and establishment of a national, and international body for the certification of socially responsible behaviour is key factor for successful implementation. The suggested at global strategy is applying model of "House of social responsibility". Effective implementation of this model requires: knowledge, resources, strategy, legislation, the supervisory body for the certification and control of social responsibility. The new industrial revolution known as Industrial 4.0 have large effect on sustainability, and it can be used as a tool for his proper applications. After COVID-19, in times of political, energetic and economic crisis, countries are faced with new challenges that require urgent solutions in order to create the conditions for the creation of socially responsible communities. The need for socially responsible behaviour increases in a situation of political, energetic and economic crisis raises with more issues and more task to solve. It requires a global change in behaviour and a revision of the existing list priorities, both for companies and for people.